Pengaruh Kepemilikan Manajerial Pada Nilai Perusahaan Dengan Pengungkapan Enterprise Risk Management Sebagai Variabel Pemoderasi - Rasmini, Ni Ketut (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 13 Nomor 2 Tahun 2019, 2019)
This study aims to examine the effect of managerial ownership on the value of the firm with enterprise risk management (ERM) as moderating variable. This research using secondary data that obtain from Manufacturing company that listed on Indonesian Stock Exchange on the period of 2013-2015. The sample was determined by purposive sampling technique with final sample of 57 observations. The hypothesis was tested using Moderated Regression Analysis for panel data by using Fixed Effect Model (FEM).  The test results show that ERM disclosure strengthen the effect of managerial ownership on the value of the firm. This result indicating supporting the signaling theory, agency theory, and the importance of ERM disclosure for the management investor, creditor and regulator related to the impact of management ownership on the value of the firm